Effects of two soft drinks on shear bond strength and adhesive remnant index of orthodontic metal brackets. - Soodabeh Sadat Sajadi; Gholamreza Eslami Amirabadi; Sepideh Sajadi (Tehran University of Medical Sciences, 2014)
Bond failure of brackets during orthodontic treatment is a common problem; which results in treatment interference, increased treatment time and prolonged clinical time for rebonding of failed brackets. The purpose of this study was to evaluate the effects of Coca-Cola and a non-alcoholic beer on the shear bond strength and adhesive remnant index (ARI) of orthodontic metal brackets in vitro.Eighty intact human premolars were divided into two experimental groups of Coca-Cola and non-alcoholic beer (Istak), and a control group of artificial saliva. Over a period of thirty days, the test groups were immersed in the respective soft drinks for 5 minutes, twice a day. For the remainder of the time, they were kept in artificial saliva at 37°C. The control group was stored in artificial saliva during the experiment. All samples were subjected to shearing forces using Universal Testing Machine. ARI was determined with a stereomicroscope at ×12 magnification. The data of shear bond strength were statistically analyzed by one-way ANOVA and Tukey's Post-Hoc test and the data of ARI scores were analyzed by Kruskal-Wallis test.No significant difference was observed in ARIs of the three groups (P≤ 0.552). The shear bond strength of Coke group was significantly lower than that of the two other groups (P≤ 0.035); but there was no significant difference between the shear bond strength of Istak and the control group (P≤ 0.999).Coca-Cola decreased the shear bond strength of orthodontic brackets.